2021
DOI: 10.1016/j.immuni.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Immune dysregulation and autoreactivity correlate with disease severity in SARS-CoV-2-associated multisystem inflammatory syndrome in children

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a life-threatening post-infectious complication occurring unpredictably weeks after mild or asymptomatic SARS-CoV-2 infection. We profiled MIS-C, adult COVID-19, and healthy pediatric and adult individuals using single-cell RNA sequencing, flow cytometry, antigen receptor repertoire analysis, and unbiased serum proteomics, which collectively identified a signature in MIS-C patients that correlated with disease severity. Despite having no evidence of acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
270
4
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(311 citation statements)
references
References 58 publications
29
270
4
8
Order By: Relevance
“…Several hypotheses have been presented to explain the systemic inflammatory response and organ involvement in MIS-A/C patients, including antibody enhancement, immune complex-mediated immunopathology, superantigen-mediated immune activation, interferonopathy and others (14,16,17). A recent study performing cytokine profiling in plasma from nine MIS-C patients identified signatures of inflammation (IL-18 and IL-6), lymphocytic and myeloid chemotaxis and activation (CCL3, CCL4, and CDCP1), and mucosal immune dysregulation (IL-17A, CCL20, and CCL28) (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several hypotheses have been presented to explain the systemic inflammatory response and organ involvement in MIS-A/C patients, including antibody enhancement, immune complex-mediated immunopathology, superantigen-mediated immune activation, interferonopathy and others (14,16,17). A recent study performing cytokine profiling in plasma from nine MIS-C patients identified signatures of inflammation (IL-18 and IL-6), lymphocytic and myeloid chemotaxis and activation (CCL3, CCL4, and CDCP1), and mucosal immune dysregulation (IL-17A, CCL20, and CCL28) (15).…”
Section: Discussionmentioning
confidence: 99%
“…Biologically relevant pathways and functions were chosen based on available literature on MIS-C, given that the MIS-A literature is currently very limited. Dysregulated NK cell, CD8+ T cell, and CD4+ T cell responses have been described in MIS-C, as well as prolonged plasmablast responses and presence of autoantibodies (14,16,21), thus genes related to adaptive and humoral immune responses were investigated. MIS-C is also characterized by hyperinflammation (14,22), prompting examination of genes involved in both inflammatory and anti-inflammatory pathways.…”
Section: Dna Isolation and Whole Exome Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 Further, in our cohort either NK cell frequency or CD56+CD16+ distribution was able to discriminate between AS and SY patients. In line with this, Ramaswamy et al 34 found that NK and CD8+ T‐cell phenotype characteristics alone are not sufficient to define the highly symptomatic/severe cases of SARS‐CoV‐2 (eg, MIS‐C), but a deepen study on cytotoxicity genes is required.…”
Section: Discussionmentioning
confidence: 99%
“…(2) There appears to be an expansion of a unique TCR repertoire (TRBV11) consistent with a super antigen selection process in patients with MIS-C ( Porritt et al., 2021 ; Ramaswamy et al., 2021 ). (3) A few groups have documented the presence of increased levels of antibodies targeting autoantigens expressed by target organs of MIS-C pathology ( Consiglio et al., 2020 ; Gruber et al., 2020 ; Ramaswamy et al., 2021 ).…”
Section: Main Textmentioning
confidence: 99%